2011
DOI: 10.1111/j.1365-3156.2011.02878.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron content of Cambodian foods when prepared in cooking pots containing an iron ingot

Abstract: Summaryobjectives To investigate the effect of cooking with an iron ingot on the iron content of several water and Cambodian food preparations.methods Various food and water samples were prepared, in replicate, in glass and aluminium pots with and without an iron ingot. The samples were subjected to iron content analysis using standard ICP-OES procedures.results Prepared with an ingot, the iron content was 76.3 lg iron ⁄ g higher in lemon water, 32.6 lg iron ⁄ g higher in pork soup and 3.3 lg iron ⁄ g higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Importantly, children are not able to ingest the ingot itself because of its size relative to the mouth of a child, therefore concerns with iron toxicity seen in children who may accidentally consume large quantities of conventional oral iron supplements are not present. While it is possible that some children may suck on the iron ingot, it is unlikely that this may result in accidental overexposure, as previous research has shown that conditions such as an acidic state, prolonged cooking time (10 minutes), high temperature and appropriate medium (water or soup) is essential for the release of meaningful quantities of iron [5]. Adverse effects of using the ingot were neither reported by the participants, nor observed by the research team.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Importantly, children are not able to ingest the ingot itself because of its size relative to the mouth of a child, therefore concerns with iron toxicity seen in children who may accidentally consume large quantities of conventional oral iron supplements are not present. While it is possible that some children may suck on the iron ingot, it is unlikely that this may result in accidental overexposure, as previous research has shown that conditions such as an acidic state, prolonged cooking time (10 minutes), high temperature and appropriate medium (water or soup) is essential for the release of meaningful quantities of iron [5]. Adverse effects of using the ingot were neither reported by the participants, nor observed by the research team.…”
Section: Discussionmentioning
confidence: 86%
“…The ability of the ingot to leach iron into food and water samples has been reported elsewhere [5]. Briefly, under realistic cooking conditions approximately 76 μg/g more iron was released in slightly acidified water when compared to a control, correlating to nearly 75% of iron requirements for women 10-49 years of age with daily requirements of 15 mg iron and with an estimated 10% bioavailability [5][6][7].…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…By 400 BCE iron largely replaced bronze and ceramic as the principle material for cooking vessels (Wells, 1984). Cooking in iron pots results in some iron uptake in the food, particularly when cooking dairy products (Kröger‐Ohlsen et al, 2002; Geerligs et al, 2003; Charles et al, 2011; Adeniyi and Ajayi, 2013; Kulkarni et al, 2013). As milk begins to sour, lactic acid bacteria can accidently or purposefully be added to the mixture to begin the fermentation process (Kunji et al, 1996).…”
Section: Discussionmentioning
confidence: 99%